Ethnicity and health-related quality of life in the post stroke population: a systematic review - Ying Xing Lee; Cornelie D. Andela; Korné Jellema; Johannes W. Schoones; Thea P. M. Vliet Vlieland; Henk J. Arwert (Journal of Rehabilitation Medicine)
Background/Objective: A systematic review was conducted on the association between ethnicity and health-related quality of life in post-stroke populations.